Bamboo slicing machine design to increase skewer production - Erwin Yuli Susanto; Mulyadi Mulyadi; Arasy Fahruddin; Iswanto Iswanto (Universitas Muhammadiyah Metro, 2022)
Sate is one of the Indonesian specialties whose demand is increasing, so the need for skewers is also getting higher. For this reason, innovation is needed to be able to meet these needs. Because when using skewers in a traditional/manual production method, the quality of the skewers produced is not good and the production capacity is also low. Meanwhile, the existing skewer making machine still has some drawbacks. So in this study, a bamboo cutting machine was designed to increase the production of skewers with innovations to cover the shortcomings of existing machines. In this study, the skewer making machine was designed to have a slicing section, a shavings section (making skewers), and a sharpening section. The skewers produced have a diameter between 2.5 mm to 3 mm and a length of 210 mm with a production capacity of 3000 skewers per hour.